Responding to the Challenges of the Modern Era through Strengthening the Pesantren Economy for Educational Quality Enhancement - Fitri Nur Rohmah; Akhmad Fauzi Sayuti (Ta'amul: Journal of Islamic Economics, 2025)
The main problem underlying this research is the number of pesantren that are not economically independent so that it depends on the help of the government, large contributions from santri, and charity. The formula of the problem in this study is to uncover how Homastas (as one of the economic ventures of Mambaul Ulum Bata-Bata) in sustaining the economic independence of pesantren and how its development strategy. The approach in this study was conducted with the qualitative method of single case studies in supermarket Homastas cottage pesantren Mambaul Ulum Bata-Bata Pamekasan Madura. Data is collected by observation methods, in-depth interviews, and archival document studies. Respondents in this study include the board of momisaris, director, unit manager, employee, alumni, and santri. Data is analyzed and checked its validity by triangulation method. The results of the study showed that Homastas played a very important role in the development of Pesantren's economy. Since its establishment in 2018, it has 16 branches and has been proven to support financial pesantren in the field of smooth education, development, and other facilities. The main strategy is to realize supermarkets managed with good and measurable management implementation, provide comfort to customers, and open branches in many places by maximizing the spread of alumni in 4 districts in Madura. Business continuity should be followed by cultivating integrity attitudes and maintaining the values of pesantren in its business practices. These findings contribute to the development of the theory of pesantren economics that one of the key to the economic independence of pesantren is the leadership of kiai and religious values integrated with modern management patterns.